Policy Rules in the Economic and Monetary Union - Bodo Herzog; Minjae Choi (Intereconomics, 2017)
This paper studies whether a monetary union can be managed solely by a rule-based approach. The Five Presidents' Report of the European Union rejects this idea. It suggests a centralisation of powers. We analyse the philosophy of policy rules from the vantage point of the German economic school of thought. There is evidence that a monetary union consisting of sovereign states is well organised by rules, together with the principle of subsidiarity. The root cause of the euro crisis is rather the weak enforcement of rules, compounded by structural problems. Therefore, we suggest a genuine rule-based paradigm for a stable future of the Economic and Monetary Union.
Keywords: 330